CONHECIMENTO PEDAGÓGICO DO CONTEÚDO NO ENSINO DE GEOMETRIA ELEMENTAR: CONTRIBUIÇÕES DE UM ESPAÇO FORMATIVO - LARA, Débora da Silva de (2019)
This research aims to analyze the contributions of a continued formation space of Mathematics teachers provides in the construction of the Pedagogical Content Knowledge in Elementary Geometry. The theoretical basis selected for the work is supported on the knowledge base of the teacher needed for teaching, especially the Pedagogical Content Knowledge (PCK), proposed by David Lee Shulman (1986, 1987). For this research, the focus will be on the Pedagogical Content Knowledge, as it refers to the dimension and capacity that the teacher has for teaching mathematics. The work methodology consists of two stages: the first one refers to the analysis of the videos recorded in meetings, here named episodes, in which the central theme approaches concepts of Geometry in a discipline entitled: 'Mathematics in the early years: contents and production of activities ". The second stage includes the application of a questionnaire and the critical evaluations of the students participating in the space of continued training, in order to understand how they manifest their pedagogical knowledge of the content and how they perceive the pedagogical knowledge of the content coming from the teacher that leads this space. The complexity of the PCK and the fact that it is built in real classroom situations makes its construction difficult for teachers who do not have experience, but we believe it is possible to provide them with a "favorable condition" for the construction and development of PCK in formations instigate this knowledge. We believe that by finalizing this research, we develop a new perception by looking at the needs that Early Years teachers encounter in teaching Geometry. Thus, the discussions about elementary concepts of Geometry, which were highlighted here, reveal that the participating teachers expressed their desire to understand the curriculum, the strategies and mathematical concepts derived from the content, revealing the construction of the PCK